Acute human brain responses to intracortical microelectrode arrays: challenges and future prospects - Fernández, Eduardo; Greger, Bradley; House, Paul A.; Aranda, Ignacio; Botella, Carlos; Albisua, Julio; Soto-Sánchez, Cristina; Alfaro, Arantxa; Normann, Richard A. (Frontiers in Neuroengineering, 2014)
The emerging field of neuroprosthetics is focused on the development of new therapeutic interventions that will be able to restore some lost neural function by selective electrical stimulation or by harnessing activity recorded from populations of neurons. As more and more patients benefit from these approaches, the interest in neural interfaces has grown significantly and a new generation of penetrating microelectrode arrays are providing unprecedented access to the neurons of the CNS. These microelectrodes have active tip dimensions that are similar in size to neurons and because they penetrate the nervous system, they provide selective access to these cells (within a few microns). However, the very long-term viability of chronically implanted microelectrodes and the capability of recording the same spiking activity over long time periods still remain to be established and confirmed in human studies. Here we review the main responses to acute implantation of microelectrode arrays, and emphasize that it will become essential to control the neural tissue damage induced by these intracortical microelectrodes in order to achieve the high clinical potentials accompanying this technology.